Anxious-depressive symptoms and sleep quality in scholarship students at a private university in Piura, Peru - Castillo Horna, Javier Ignacio (2024)
Objective: To evaluate the association between anxiuos-depressive symptoms and sleep quality in scholarship students of the University of Piura belonging to Programa Beca 18. Methods: Cross-sectional observational study that used the Pittsburgh Sleep Quality Index (PSQI), the Zung's Self-Anxiety Scale (SAS) and the Zung Depression Scale (SDS). Results: 293 students participated in the study. The greater the anxiety-depressive symptoms, the worse the quality of sleep in the students. We found a significant relationship between anxiety symptoms and poor quality of sleep (p<0.005) and depressive symptoms and poor quality of sleep (p<0.005). Conclusions: There is a significant tendency for Beca 18 university students with anxious-depressive symptoms to have poor sleep quality.